Segregation of glutamatergic and cholinergic transmission at the mixed motoneuron Renshaw cell synapse - Boris Lamotte d’Incamps; Gardave S. Bhumbra; Joshua D. Foster; Marco Beato; Philippe Ascher (Scientific Reports, 2017)
Abstract In neonatal mice motoneurons excite Renshaw cells by releasing both acetylcholine (ACh) and glutamate. These two neurotransmitters activate two types of nicotinic receptors (nAChRs) (﻿the homomeric α7 receptors and the heteromeric α*ß* receptors) as well as the two types of glutamate receptors (GluRs) (AMPARs and NMDARs). Using paired recordings, we confirm that a single motoneuron can release both transmitters on a single post-synaptic Renshaw cell. We then show that co-transmission is preserved in adult animals. Kinetic analysis of miniature EPSCs revealed quantal release of mixed events associating AMPARs and NMDARs, as well as α7 and α*ß* nAChRs, but no evidence was found for mEPSCs associating nAChRs with GluRs. Bayesian Quantal Analysis (BQA) of evoked EPSCs showed that the number of functional contacts on a single Renshaw cell is more than halved when the nicotinic receptors are blocked, confirming that the two neurotransmitters systems are segregated. Our observations can be explained if ACh and glutamate are released from common vesicles onto spatially segregated post-synaptic receptors clusters, but a pre-synaptic segregation of cholinergic and glutamatergic release sites is also possible.